Rubber seed oil - Martin G
Rubber seed contains about 25;il and it is reported that an American company used about 8000M.T. of this oil in 1928 for various applications. Rubber seed deteriorates very fast and the oil extracted from such seeds is inferior in quality and suitable for the production of soft soap. Raising the temperature of the seed to 100degree C for a minute can prevent the deterioration of the seed quality oil can be prepared from it. It was estimated that the total seed production in Malaya can yield about 60,000 M.T. of oil and hence proper collection of the seedds need to be organized availing the free time of the labourers and small farmers.
Keywords: Rubber seed oil